A novel strain of cynomolgus macaque cytomegalovirus: implications for host-virus co-evolution. (December 2016) - Russell, Justen; Marsh, Angie; Willer, David; Ambagala, Aruna; Dzamba, Misko; Chan, Jacqueline; Pilon, Richard; Fournier, Jocelyn; Brudno, Michael; Antony, Joseph; Sandstrom, Paul; Evans, Ben; et al.
Abstract Background Cytomegaloviruses belong to a large, ancient, genus of DNA viruses comprised of a wide array of species-specific strains that occur in diverse array of hosts. Methods In this study we sequenced the 217 Kb genome of a cytomegalovirus isolated from a Mauritius cynomolgus macaque, CyCMV Mauritius, and compared it to previously sequenced cytomegaloviruses from a cynomolgus macaque of Filipino origin (CyCMV Ottawa) and two from Indian rhesus macaques (RhCMV 180.92 and RhCMV 68–1). Results Though more closely related to CyCMV Ottawa, CyCMV Mauritius is less genetically distant from both RhCMV strains than is CyCMV Ottawa. Several individual genes, including homologues of CMV genesRL11B, UL123, UL83b, UL84 and a homologue of mammalian COX-2, show a closer relationship between homologues of CyCMV Mauritius and the RhCMVs than between homologues of CyCMV Mauritius and CyCMV Ottawa. A broader phylogenetic analysis of 12 CMV strains from eight species recovers evolutionary relationships among viral strains that mirror those amongst the host species, further demonstrating co-evolution of host and virus. Conclusions Phylogenetic analyses of rhesus and cynomolgus macaque CMV genome sequences demonstrate co-speciation of the virus and host.